Tanggung Jawab Perusahaan Penyedia Jasa Transportasi Online Terhadap Keselamatan Penumpang Berdasarkan Undang- Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan Di PT. Gojek Indonesia - Wulan Berlianti; Pamungkas Satya Putra (Peneliti.net, 2023)
The development of online application-based transportation services that offer services for the transportation of people and/or goods which were introduced in 2015. The ease of online application-based transportation is also inseparable from the emergence of problems. Based on this, the author intends to conduct research with the aim of knowing the responsibilities of companies providing online transportation services to passengers in the event of an accident, to examine the legal position of companies providing online transportation services in applicable laws and regulations, to describe how legal protection forms for service providers. Online Transportation Against Accident Passengers.The research method used in writing this thesis is normative juridical which is carried out by examining secondary data consisting of primary, secondary and tertiary legal materials. Data collection techniques are carried out by means of literature study. The data that has been obtained is analyzed qualitatively. Based on the results of the research, the authors conclude that online motorcycle taxis are not a public transportation company regulated in Article 47 paragraph (3) of Law Number 22 of 2009 concerning Road Traffic and Transportation because two-wheeled vehicles are not included in the general motorized vehicles referred to in the article. . With the enactment of the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 108 of 2017, this is the basis for online motorcycle taxis to operate. The responsibilities of online motorcycle taxi application provider companies in the transportation sector cannot be equated with the responsibilities of public transportation companies. Responsibilities between application provider companies and service providers are equal and jointly responsible.